Taxonomic Studies of the Rotifera from Shallow Waters on the Island of Maracá, Roraima, Brazil - Koste, Walter; Robertson, Barbara (Amazoniana, 1990)
Four samples collected in the periodicaily dry, shallow water ecosystems on the island of Maracá (Roraima, Brazil) were investigated for rotifers. This survey is the first in the area. 159 species were identified and the rotifer community is characteristic of smdl bodies of water with decomposing vegetation.
Keywords: Vegetação em Decomposição